PENDIDIKAN KESEHATAN KEBUTUHAN ISTIRAHAT TIDUR PADA MASA PANDEMI BAGI REMAJA - Yustina Kristianingsih; Sri Winarni (Jurnal Pengabdian Kepada Masyarakat ITK (PIKAT), 2023)
Corona virus 19 (COVID 19) is now a word that is often heard and is a problem in Indonesia and the world. The existence of the COVID-19 pandemic has forced changes in the implementation of various activities such as Work From Home, School From Home and others. School from Home or known as Distance Learning (PJJ) makes students have to study from home and use tools such as laptops / phonecell that can have an impact on health, one of which is sleep disorders. Sleep problems in adolescence will affect the growth and development of adolescents. So it is important to be given health education about the need for sleep rest and how to regulate sleep patterns during the COVID 19 pandemic. The purpose of this activity is to increase adolescent knowledge about the need for sleep rest and how to regulate sleep patterns. The target of this activity is 40 Catholic youths in the Sakramen Mahakusus Church in Surabaya. Health education is carried out online with the Zoom application,health education methods used question and answer and assistance via group/personal Whatsapp. Adolescents are very active in health education activities and many questions are asked. The results of the evaluation before and after health education showed an increase in the knowledge of teenagers in the Sacrament Mahakudus church Surabaya parish about the need for sleep and how to regulate sleep patterns during the COVID-19 pandemic.